2007
DOI: 10.3748/wjg.v13.i9.1431
|View full text |Cite
|
Sign up to set email alerts
|

Surgical approaches of resectable synchronous colorectal liver metastases: Timing considerations

Abstract: AIM:To compare the safety and efficacy of simultaneous versus two stage resection of primary colorectal tumors and liver metastases. METHODS:From January 1996 to May 2004, 103 colorectal tumor patients presented with synchronous liver metastases. Twenty five underwent simultaneous colorectal and liver surgery and 78 underwent liver surgery 1-3 mo after primary colorectal tumor resection. Data were retrospectively analyzed to assess and compare the morbidity and mortality between the surgical strategies. The tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
1
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 26 publications
3
47
1
5
Order By: Relevance
“…In the patients undergoing staged resections, the metastases were generally larger and more numerous ( Table 2). There was a general tendency towards extending the criteria for synchronous resections over time, and the newer studies reported a greater number of major hepatectomies (more than three segments) in the more recent years [9][10][11][12]. For the reason of this clinical heterogeneity, no pooled estimates were undertaken.…”
Section: Resultsmentioning
confidence: 99%
“…In the patients undergoing staged resections, the metastases were generally larger and more numerous ( Table 2). There was a general tendency towards extending the criteria for synchronous resections over time, and the newer studies reported a greater number of major hepatectomies (more than three segments) in the more recent years [9][10][11][12]. For the reason of this clinical heterogeneity, no pooled estimates were undertaken.…”
Section: Resultsmentioning
confidence: 99%
“…The 5-year survival after liver resection varies between 16% and 30% [5, 710]. The tumour recurrence rate after resection of hepatic metastases varies between 40.4% and 73.5% [11, 12].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the need for only one operation improves the patient's comfort, reduces healthcare costs, and overall hospital stay [3,11] . Some studies have indicated that simultaneous resection of the colorectal primary lesion and hepatic metastasis is safe and acceptable [3,5,10,[26][27][28] . Martin et al [3] analyzed the severity of complications with both major and minor liver resections as well as similar colorectal procedures and found no statistical difference between the results from the 2 groups.…”
Section: Discussionmentioning
confidence: 99%